2019
DOI: 10.1002/bjs.11221
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of randomized clinical trials of early versus delayed cholecystectomy for mild gallstone pancreatitis

Abstract: Background: Gallstones account for 30-50 per cent of all presentations of acute pancreatitis. While the management of acute pancreatitis is usually supportive, definitive treatment of gallstone pancreatitis is cholecystectomy. Guidelines from the British Society of Gastroenterology suggest definitive treatment on index admission or within 2 weeks of discharge, whereas joint recommendations from the International Association of Pancreatology and the American Pancreatic Association recommend definitive treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 33 publications
(86 reference statements)
2
20
0
2
Order By: Relevance
“…We retrieved the latest evidence for a metaanalysis of a randomized controlled study. It was found that for mild biliary pancreatitis, previous studies have confirmed that cholecystectomy at the same time of hospitalization can reduce the recurrence rate of pancreatitis (23).…”
Section: Timing Of Cholecystectomymentioning
confidence: 92%
“…We retrieved the latest evidence for a metaanalysis of a randomized controlled study. It was found that for mild biliary pancreatitis, previous studies have confirmed that cholecystectomy at the same time of hospitalization can reduce the recurrence rate of pancreatitis (23).…”
Section: Timing Of Cholecystectomymentioning
confidence: 92%
“…[13][14][15] Similarly, Moody et al, in a meta-analysis study, observed that early cholecystectomy reduced the frequency of readmissions due to biliary complications, among individuals with previous episodes of acute biliary pancreatitis. 16 The duration of obstruction was significantly associated with the severity of both cholestasis and ductular proliferation. This highlights the progressive aspect of these changes in relation to the duration of the causative condition and, of course, emphasizes the importance of early treatment in order to avoid the development of chronic disease.…”
Section: Discussionmentioning
confidence: 95%
“…Based on this trial, cholecystectomy is recommended during the index admission in patients with mild ABP. Failure to remove the gallbladder on index admission resulted in an increase in gallstone‐related complications such as pancreatitis, biliary colic and readmissions, as confirmed in a meta‐analysis. With respect to conversion rates from laparoscopy to laparotomy or surgical complexity, no differences between groups were detected.…”
mentioning
confidence: 81%